Chemoprevention and cancer in the brazilian context: From healthiness to diagnosis (Research, Society and Development, 2021)
Cancer represents one of the biggest public health problems in the world. Despite increasing advances and occasional successes, patients and healthcare professionals continue to face numerous setbacks from cancer therapy. In this direction, the concept of chemoprevention is intuitively instigating, as it implies avoiding suffering from cancer, having a potential effect before diagnosis, on prognosis and also on treatment. The goal of this review is to list the main possible chemopreventive approaches, at primary, secondary and tertiary levels, for the most frequent tumors in Brazil, which have a strong correlation with everyday habits adopted. To achieve that, a bibliographic survey of the publications available in the databases of the National Library of Medicine (NIH - PubMed) and Scholar Google for the last 20 years was carried out. The descriptors used were: “chemoprevention”, “cancer chemoprevention”, “non melanoma skin cancer”, “lung cancer”, “breast cancer”, and “colorectal cancer”. The results obtained by several in vitro and in vivo studies are remarkable, as well as the clinical success stories. Nevertheless, the challenges are still many, due, mainly, to the variables found in the individual responses of the patients, which can be influenced by specificities of the clinical condition, as well as investment limitations and adherence. Future research and investment in education and awareness of both the general public and health professionals, regarding the benefits behind cancer chemoprevention, would enable the wide application of chemoprevention and benefit several areas of healthcare.